THERMOOPTIC COEFFICIENTS MEASUREMENTS BY A LASER BEAM DEVIATION METHOD FOR THE MEDIUM WITH LINEAR THERMAL GRADIENT - P. A. Loiko; K. V. Yumashev; N. V. Kuleshov; A. A. Pavlyuk (Приборы и методы измерений)
The experimental setup for thermooptic coefficients dn/dT measurements by a laser beam deviation method for the medium with linear thermal gradient was developed. By means of this approach, the dispersion of the dn/dT values in the optically biaxial potassium gadolinium tungstate crystal KGd(WO4)2 was investigated in the 0,4–1,06 μm spectral range for light polarized along the principal directions in the crystal.